2020
DOI: 10.3389/fpsyg.2020.00201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Angle of View and Partial Sleep Deprivation on Distance Perception

Abstract: The present study aimed to investigate the effects of intensive effort on egocentric distance perception according to different angles of view after sleep deprivation at the beginning (SDB) or at the end (SDE) of the night and after a normal sleep night (NNS). Ten male students soccer players (age 22.8 ± 1.3 years; body mass 72.0 ± 10.4 kg; body height 180.0 ± 3.0 cm) performed a repeated cycling (RS) exercise (10 × 6 s maximal cycling with 24 s in between) after SDB, SDE, and NNS. They were asked to estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…For clarity, the match analysis included two studies that analyzed load from matches with relationship with sleep [ 31 , 32 ]. Athletic performance included 15 studies that applied different experimental designs through physical tests to analyze its influence on sleep [ 20 , 27 , 28 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Training load included six studies that observed training effects on sleep [ 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For clarity, the match analysis included two studies that analyzed load from matches with relationship with sleep [ 31 , 32 ]. Athletic performance included 15 studies that applied different experimental designs through physical tests to analyze its influence on sleep [ 20 , 27 , 28 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Training load included six studies that observed training effects on sleep [ 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The most-used instrument to analyze sleep was actimetry, applied in twelve studies [ 8 , 9 , 10 , 17 , 18 , 20 , 33 , 38 , 39 , 40 , 41 , 47 ]. In addition, 25 studies included sleep logs/questionnaires to analyze its quantity and/or quality [ 10 , 17 , 18 , 19 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 48 , 49 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we aimed to study inter-individual and inter-specific variation in neophobia in ungulates. Ungulates are a largely neglected taxon in comparative psychology, despite their high variation in socio-ecological characteristics, which makes them an ideal candidate to test how specific socio-ecological conditions may favor the emergence of certain traits or behaviors (Caicoya et al in review; see Shultz and Dunbar 2006 ; Schaffer et al 2020 ). In this study, we tested neophobia toward novel objects (see Greenberg 1992 ; Mettke-Hofmann et al 2002 ; Greenberg 2003 ; Brown and Jones 2016 ) by providing ten ungulate species with familiar food, half of which had been positioned close to a novel object.…”
Section: Introductionmentioning
confidence: 99%